Use of the FINCAS Application to Assess the Sustainability of Pineapple (Ananas comosus L.) Production Systems in Aguazul (Colombia) - Sánchez-Rojas, Edwin Fernando; Cárdenas-Cárdenas, María Alejandra; Ramos-Cruz, Martha Lucía (Universidad Pedagógica y Tecnológica de Colombia, 2023)
Agroecological transition processes are the strategies that will ensure a sustainable future for human food and diverse life on Earth. This research presents results of using the FINCAS application, a digital tool to assess the sustainability of agroecosystems in situ. The software was used to evaluate the productive system of pineapple (Ananas comosus L.) in Aguazul (Colombia), under the snowball sampling method. A total of 32 farms were obtained, of which 46.9 % are in high sustainability categories; 40.6 % in transition towards sustainability and 12.5 % in low sustainability categories. The results show that farms with low sustainability need to integrate production systems, increase the supply of food produced on the farm, and use the agro-industrial success stories in the pineapple production chain, to introduce ways of using all available resources that reduce dependence on external inputs.